Disagreement-induced CEO turnover - Huang, Sheng; Maharjan, Johan; Thakor, Anjan V. (Journal of Financial Intermediation, 2020)
We propose and test a new explanation for forced CEO turnover, and examine its implications for the impact of firm performance on CEO turnover. Investors may disagree with management on optimal decisions due to heterogeneous prior beliefs. Theory suggests that such disagreement may be persistent and costly to firms; we document that this induces them to sometimes replace CEOs who investors disagree with, controlling for firm performance. A lower level of CEO-investor disagreement serves to partially “protect” CEOs from being fired, thus reducing turnover-performance sensitivity, which we also document. We also show that firms are more likely to hire an external CEO as a successor if disagreement with the departing CEO is higher. Disagreement declines following forced CEO turnover. Using various empirical strategies, we rule out other confounding interpretations of our findings. We conclude that disagreement, independently of firm performance, affects forced CEO turnover.